A Household-Based Cross-Sectional Survey of Knowledge, Awareness and Practice Regarding Malaria in Western Area Rural District, Sierra Leone - Wang, Lili; Yin, Jianhai; Zheng, Canjun; Smith, Samuel Juana; Ngegba, Esther; Huang, Xiaoxia; Kamara, Anitta; Chen, Xia; Wang, Xu; Luo, Wei; Kan, Biao (Frontiers in Public Health, 2021)
Sierra Leone is a highly endemic area for malaria, and the implementation of the National Malaria Strategic Plan (2016-2020) has reached its midpoint in 2018. To provide more specific guidance for interventions in the future, a household-based cross-sectional survey was conducted to elucidate the knowledge, awareness and practices regarding malaria and malarial control measures among the general public. Three communities (Grafton, Jui and Kossoh) in the Western Area Rural District that were in close proximity to Sierra Leone’s capital city of Freetown were included. Households were randomly selected and interviewed with a structured questionnaire covering malaria infection, diagnosis, treatment and prevention, as well as knowledge of malaria prevention. As a result, a total of 262 qualified questionnaires were included. The average cost for meals per day is approximately 30000 Leones in each household. The rate of awareness, indicated by reporting having heard of malaria, was 98.1% (257/262), and 86.6% (227/262) of the respondents knew that mosquito bites are the main route of transmission. In addition, 80.9% (212/262) of the respondents sought health advice or treatment for the illness, and a similar percentage of respondents had been tested for malaria, mostly with rapid diagnostic tests (RDTs). A high demand for long-lasting insecticidal nets (72.1%) matched the serious shortage (61.8%, 162/262), and of the households that reported a lack of nets, 66 had children younger than five years old. In conclusion, public awareness of malaria prevention is high, based on this survey, although there was a limited use of preventive measures in these three communities and the malaria burden was still high. Therefore, the public’s knowledge of malaria should be sustained and reinforced, and the distribution and use of malaria prevention measures should be promoted to supprt the achievement of the planned objectives.